Visualizing domestic masculinity: Negotiation, representation, and visual absence among stay-at-home fathers - Aly Mecca; Faruk Faruk; Rachmat Hidayat (SIMULACRA: JURNAL SOSIOLOGI, 2026)
This study explores how stay-at-home fathers in Indonesia construct and negotiate masculine identities through visual practices within a social context where caregiving remains strongly associated with women and men continue to be positioned as primary breadwinners. Using a photo-elicitation method, 17 participants documented their domestic experiences through self-produced photographs, archival images, and reflective interviews. The findings show that domestic masculinity is not a fixed category but a spectrum of representations shaped through everyday practices, emotional presence, symbolic expressions, and visual absence. Participants articulated their roles through domestic labor, relational engagement with children, and metaphorical imagery that rearticulated masculine values such as strength, responsibility, and protection within the domestic sphere. At the same time, tensions persisted between caregiving and expectations surrounding men’s economic provision, suggesting that domestic masculinity is continuously negotiated rather than fundamentally transformed. In some instances, the absence of images highlighted the limits of representation, including concerns surrounding privacy, legitimacy, and self-perception. Photography functioned as a reflective and representational medium through which participants negotiated masculinity in everyday domestic life. The study contributes to discussions on domestic masculinity and visual representation in Southeast Asian contexts, while also highlighting the importance of considering visual negotiation, selective visibility, and social legitimacy in future studies of fatherhood and caregiving.